2004
DOI: 10.1063/1.1773928
|View full text |Cite
|
Sign up to set email alerts
|

Attachment losses of high Q oscillators

Abstract: Attachment losses can play a role in limiting the quality factors of micro/nanomechanical oscillators. The existing theoretical results in this regard are applicable to highly idealized scenarios. The theory has been extended in two important directions: the width of the cantilever is considered to be small relative to a wavelength as opposed to large, and the base is allowed to have finite thickness. These extensions result in significant, in many cases order of magnitude, changes in the estimates of attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 14 publications
2
96
1
Order By: Relevance
“…[Pho04], and detailed numerical analysis may be required to estimate support losses. Alternately, more sophisticated designs can be employed to isolate the beam from the supports by creating free-free beams that are attached at their nodal points [Fer05].…”
Section: Theory: Calibration Using Thermoelastic Dampingmentioning
confidence: 99%
“…[Pho04], and detailed numerical analysis may be required to estimate support losses. Alternately, more sophisticated designs can be employed to isolate the beam from the supports by creating free-free beams that are attached at their nodal points [Fer05].…”
Section: Theory: Calibration Using Thermoelastic Dampingmentioning
confidence: 99%
“…There are several models [18][19][20] for quality factors limited by clamping losses, represented as Q clamping , for out of plane flexural cantilever resonators attached to supports of different dimensions. Jimbo et al 20 predicted the quality factor limited by clamping loss of cantilever beam of infinite width attached to semi-infinite base to be given by…”
Section: Dissipation In Microcantileversmentioning
confidence: 99%
“…For the base thickness ͑t b ͒ smaller than the wavelength of the elastic wave in the base ͑ b ͒, quality factors limited by clamping losses to the thickness-matching base are proportional to the aspect ratio of the levers ͑L / w͒. 18,19 However this model does not take into account the fact that thickness-matching bases can be overhangs where the energy can be reflected back to the oscillator. 18 Photiadis et al 19 developed a model for clamping losses of flexural cantilever resonators with finite…”
Section: Dissipation In Microcantileversmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it has been demonstrated that not only the nature of the clamping but also its geometry greatly determines the amount of energy that is lost through the clamping. 42,43 Therefore, lower values of F min should be achievable through the optimization of the size of the rods (by reducing their thickness) and their clamping geometry (by reducing its curvature radius or increasing the lateral size of the supporting medium).…”
mentioning
confidence: 99%